PELATIHAN DAN PENDAMPINGAN PENGOLAHAN PRODUK PANGAN (BERBAHAN IKAN LELE) DAN TEKNIK PEMASARAN BAGI PENGURUS LEMBAGA KESEJAHTERAAN SOSIAL ANAK (LKSA) WIDHYA ASIH DI DESA CICA, MENGWI, BADUNG, BALI - Ni Made Erpia Ordani Astuti; I Gusti Ayu Ika Monika Pranstyandhari; I Gede Deddy Rahmat (Jurnal Nirta : Inovasi Multidisiplin, 2026)
Widhya Asih Badung is a Children’s Social Institution ‘Lembaga Kesejahteraan Sosial Anak (LKSA)’ which is under Widhya Asih Bali Sejahtera Foundation whose mission is “Breaking the chain of poverty in society through caring for underprivileged children in order to create superior human resources and have a better future”. The institution, which is located at Jl. Sang Hyang, Br. Cica, Abianbase, Mengwi, raises 23 children with underprivileged economy and other different backgrounds. One of them is in grade one of elementary school, six are in junior high school, and eleven are in vocational high school. They carry out simple and creative economic activities; namely, they sell food products through “PAON LKSA”. The institition was founded during the Covid-19 pandemic. Until now they have been receiving orders for food and snacks both on a large- and small-scale using pre-order system. The ability or skill to produce food are three things that need to be developed in order to produce food that is high quality, attractive, tasty and safe consumption. The skill and competence of the management of Lembaga Kesejahteraan Sosial Anak (LKSA)need to be developed through training and mentoring in the process of making food products from catfish. The technique of marketing the products need to be trained and mentored as well. The output of this activity includes: the management of Lembaga Kesejahteraan Sosial Anak (LKSA) Widhya Asih Badung will have the knowledge of the types of food ingredients, cooking utensils, and proper cooking method when producing catfish food products, and the technique of marketing them.